The Physical activity in the prevention and treatment of osteoporosis: From biomarkers to quality of life - Ciułek, Urszula; Bilska, Wiktoria; Żydek, Ada (Quality in Sport, 2024)
Introduction and Objective: Osteoporosis is a common skeletal disease typified by diminished bone density and deterioration of bone structure. It represents a significant risk factor for fractures, particularly in postmenopausal women. This study evaluates the role of physical activity and bone biomarkers in the prevention and treatment of osteoporosis. Review and Methods: A review of the literature was conducted with the objective of analysing the impact of weight-bearing exercise and resistance training on bone health and the use of biomarkers in diagnosing and monitoring osteoporosis. Moreover, the potential impact of dietary interventions and supplementation was examined. Abbreviated Description of the State of Knowledge: It is of the utmost importance to engage in regular physical activity, particularly weight-bearing exercises, in order to prevent and treat osteoporosis. It has been demonstrated to enhance bone density and moderate the likelihood of fracture. Biomarkers such as osteocalcin and alkaline phosphatase are of significant value in the assessment of bone health. Summary: The combination of physical activity, a balanced diet and appropriate supplementation is fundamental to the prevention and effective management of osteoporosis. This approach confers substantial benefits with respect to bone health and quality of life. Keywords: Osteoporosis; Physical activity; Bone health; Skeletal System